2017
DOI: 10.18632/oncotarget.15840
|View full text |Cite
|
Sign up to set email alerts
|

RITA displays anti-tumor activity in medulloblastomas independent of TP53 status

Abstract: Current therapy of medulloblastoma, the most common malignant brain tumor of childhood, achieves 40–70% survival. Secondary chemotherapy resistance contributes to treatment failure, where TP53 pathway dysfunction plays a key role. MDM2 interaction with TP53 leads to its degradation. Reactivating TP53 functionality using small-molecule inhibitors, such as RITA, to disrupt TP53-MDM2 binding may have therapeutic potential. We show here that RITA decreased viability of all 4 analyzed medulloblastoma cell lines, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In this study, we observed that RITA increased the p53 levels and reduced the viability and clonogenic potential of all GB cell lines, irrespectively of the TP53 mutational status. This observation is consistent with the findings of previous studies by both our group and others, showing that RITA was effective not only on p53 wild-type cells, but also on p53 mutant cells (57,60,(63)(64)(65)(66)(67)84).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we observed that RITA increased the p53 levels and reduced the viability and clonogenic potential of all GB cell lines, irrespectively of the TP53 mutational status. This observation is consistent with the findings of previous studies by both our group and others, showing that RITA was effective not only on p53 wild-type cells, but also on p53 mutant cells (57,60,(63)(64)(65)(66)(67)84).…”
Section: Discussionsupporting
confidence: 93%
“…Although RITA was initially identified as a compound preventing the p53-MDM2 interaction and inducing a p53-dependent apoptosis (40), subsequent studies failed to demonstrate RITA inhibitory effect on the p53-MDM2 interaction (42,43) and indicated that RITA can act also through p53-independent mechanisms (44)(45)(46)(47)(48)(49)57,84). Thus, in this study, to investigate the role of p53 in RITA-induced apoptosis in GB cells, we treated these cells with RITA in combination with the p53 inhibitor, PFTα, and observed that this inhibitor markedly decreased the RITA-induced apoptosis of all GB cells.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 -mutated SHH tumours are stratified as very-high risk and account for the majority of treatment failures within the SHH subgroup 25 . To explore whether differences in drug response between TP53 -wildtype and TP53 -mutated SHH medulloblastoma cells could be recapitulated in vitro, we utilised ONS76 cells ( TP53 -wildtype) and a genetically modified ONS76 cell line harbouring a dominant negative p53 mutation ( TP53 -mutant; ONS76 dnp53) 26 . We compared vincristine response in both cell types in 2D monolayer and 3D spheroid culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, reconstitution of compound-restored in vitro DNA binding demonstrates the direct mode of action for the UCI-LC0023 compound series (Figure 5D). Many of the putative p53 reactivation compounds reported in the literature have not been shown to bind p53, and the anti-cancer effects of some of the compounds have been attributed to compound effects that were independent of p53 reactivation (Gottlieb et al, 2017;Lu et al, 2016;Mobaraki et al, 2018;Patyka et al, 2016;Peng et al, 2013;Yoshikawa et al, 2016). In particular, the large class of thiol-reactive compounds such as PRIMA-1 and its clinical derivative APR-246 have recently been suggested to act mainly through induction of redox imbalance by depletion of glutathione (Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%